IMPLEMENTATION OF SALES INFORMATION SYSTEM OF INDONESIAN SPICES AT PT.INDO REMPAH - Ahmad Fauzi; Novita Indriyani; Andika Bayu Hasta Yanto (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Spices and herbs are biological resources that have long played an important role in human life. In the current pandemic where our bodies have an immune system that can manage the body's power, but the factors of age, lifestyle and regular use of drugs can affect the level of body power, therefore this spice has been considered to provide health and this has led to the demand for spices. high enough. The continuous use of spices, both from the household sector to the industrial sector, makes consumers have to find or buy these spices every day to the market or to spice collectors for industrial consumers. To meet market needs and consumer needs directly, therefore the proposed solution to overcome this problem is to use e-commerce media. The system development model used in making this information system is the SDCL (System Development Life Cycle) waterfall (Waterfall) or classic life flow. The stages that are passed in the system analysis and design process include: system requirements analysis, design, code generator, testing and support. From the results of this study, it is hoped that the existence of this spice sales information system can help farmers, especially spice producers, in terms of increasing the selling power of their agriculture, making it easier to carry out promotions, sales transactions to produce sales reports.